Hands On. - Graafstra, A.
This paper discusses the idea of a hobbyist having a radiofrequency identification (RFID) tag implanted in him. In an RFID "lock" system, each RFID tag, which is essentially a minitransmitter, sends out a sequence of radiofrequency pulses representing a unique number, usually 10 to 16 digits in length. An RFID tag's memory typically ranges from a few bits to 128 bits, in the common ISO-compliant tag, to several megabytes. There are 6 ways on how an RFID implant works:1) It emits radio waves, which powers the implanted tag when it si within range, 2) the tag, which consists of a microchip and an antenna, checks the password, 3) It transmits a code stored in its memory back to the reader, 4) the reader compares the tag's code to a key code stored in the reader, 5) the reader generates a new and stores it, then sends the new key to the tag, and 6) the tag writes the new key into its memory
Keywords: ISO-compliant tag; RFID tag implants; Minitransmitter; Radiofrequency identification; Radiofrequency pulses; Radiowave emission